Computer Technology to Improve Medical Information in Bangkok, Thailand - Jirapanthong, Waraporn (Journal of Reviews on Global Economics, 2017)
Building hospital applications based on services allow hospitals and other organizations to cooperate and make use of business functions. Hospital information systems that involve extensive information exchange across hospitals and organization boundaries, such as patient profiles, can easily be automated. Service-based applications can be constructed by linking services from various providers using either a standard programming language or a specialized workflow language. This paper reviews the use of computer technology which supports health services in Bangkok, Thailand by developing a survey of health services in hospitals, in which the focus is on the attitudes and competence of medical students and physicians, and the availability of health services equipment; and analyzing and providing guidance via a web service that supports health services. A prototype of a web application is created to simulate situations of the use of computer-based devices for supporting clinical operations, involving 12 medical doctors and 3 patients. Two cases are analysed to demonstrate different situations of the web service. In such situations, stakeholders are requested to query patient information and specify the documents. The experiments have been evaluated by considering straightforward criteria to perform activities with the prototype to determine how accurate the documents are requested and specified, and evaluate how the health service performs efficiently.